When the camera eats first: Exploring how meal-time cell phone photography affects eating behaviours. (1st November 2020) - Yong, Joceline Y.Y.; Tong, Eddie M.W.; Liu, Jean C.J.
Abstract: Advances in cell phone technology have the potential to disrupt eating patterns. In this research, we focused on the camera function of a cell phone, characterizing: (i) the extent to which this function is used during meals; (ii) whether meal-time photographers show signs of pathological eating; and (iii) whether the act of taking food photographs alters the amount and enjoyment of food eaten. In the first study, we used the experience sampling method to track one week of meals from 137 young adults. Although we observed a low base rate of meal-time photography (5.44% of the 1140 meals captured), phone users who engaged in this practice had higher external eating scores than those who did not. That is, these meal-time photographers were more likely to eat in response to external cues (e.g. the sight of palatable food) than to internal cues of hunger. However, when participants were randomly assigned to take either food or non-food photographs within a lab setting (Study 2), we found no evidence that the type of photography influenced either the amount or enjoyment of food eaten. Taken together, our findings suggest a limited role for cell phone photography in an obesogenic environment.